The Ontology of Russian Artistic Culture - Tsvetaeva, Marina N. (Actual Problems of Theory and History of Art, 2016)
A profound analysis of modern culture, in the context of its foundations and connection with the previous tradition defined by Christian ontology and anthropology, is very important for the time being. It reveals soteriological, ontological, symbolical, liturgical, psychological, ethical, and anagogical aspects. Ascetic practices and patristic literature, for example works by Archimandrite Sophronius (Sakharov), the biographer of Silouan the Athonite, state that the basis and the meaning of culture is to witness the Truth, Beauty and Good. Modern culture cannot discard heavenly, iconic, logocentric, and sofinety approaches as a basis for the creation of an artistic image. We are talking about inversions, shifting of meaning and value of the language.It is important to analyze so called “artistic forfeit” and its influence upon our cognitive abilities. We have suffered great losses: a sense of harmony, divine beauty, ability for metaphoric thinking. For example, due to the lack of spiritual and psychological content, contemporary icon-painting is in a crisis. It seems crucial to learn more about interactions between Old Russian, classical and avantgarde phases of art. Interpretations of artistic texts, “seeing” a profound meaning, the sense of the divine eternity are also actual problems of the modern culture. It is important to discuss the meaning of an artist’s responsibility, freedom of creation, spiritualism, spiritual supervision, the meaning of words and prospects of an artwork.
Keywords: the knowledge of God; apostasy; ontology; spirit and body integrity; iconicity; anti-icon; disembodiment; soteriology; prototype; Archimandrite Sophronius (Sakharov)